Math, asked by cheeko32, 8 months ago

Answer this question pls its urgent​

Attachments:

Answers

Answered by anchal1217
5

Answer:

Given : x²+=49

x-y=3

To find : x³-y³

Solution : We know that,

(a-b)² = a²-2ab+

So, (x-y)² = -2xy +

(3)² = 49-2xy (Given)

9 = 49-2xy

2xy = 49-9

2xy = 40

xy = 40/2

xy = 20

Now,

x³-y³ = (x-y)(++xy) (Given and one proved)

x³-y³ = (3)(49+20)

x³- = 207

So,the correct answer is (c)207.

Answered by Anonymous
0

Answer:

hello.............(〒﹏〒)(〒﹏〒)

Similar questions